Rapid high-resolution melting genotyping scheme for Escherichia coli based on MLST derived single nucleotide polymorphisms - Bezdicek, Matej; Nykrynova, Marketa; Sedlar, Karel; Kralova, Stanislava; Hanslikova, Jana; Komprdova, Aja; Skutkova, Helena; Kocmanova, Iva; Mayer, Jiri; Lengerova, Martina (Scientific reports, 2021)
Routinely used typing methods including MLST, rep-PCR and whole genome sequencing (WGS) are time-consuming, costly, and often low throughput. Here, we describe a novel mini-MLST scheme for Eschericha coli as an alternative method for rapid genotyping. Using the proposed mini-MLST scheme, 10,946 existing STs were converted into 1,038 Melting Types (MelTs). To validate the new mini-MLST scheme, in silico analysis was performed on 73,704 strains retrieved from EnteroBase resulting in discriminatory power D = 0.9465 (CI 95% 0.9726-0.9736) for mini-MLST and D = 0.9731 (CI 95% 0.9726-0.9736) for MLST. Moreover, validation on clinical isolates was conducted with a significant concordance between MLST, rep-PCR and WGS. To conclude, the great portability, efficient processing, cost-effectiveness, and high throughput of mini-MLST represents immense benefits, even when accompanied with a slightly lower discriminatory power than other typing methods. This study proved mini-MLST is an ideal method to screen and subgroup large sets of isolates and/or quick strain typing during outbreaks. In addition, our results clearly showed its suitability for prospective surveillance monitoring of emergent and high-risk E. coli clones'.
Keywords: genom bakteriální; infekce vyvolané Escherichia coli; Escherichia coli Infections; denaturace nukleových kyselin; Polymorphism, Single Nucleotide; surveillance populace; DNA bakterií; DNA primery; repetitivní sekvence nukleových kyselin; Multilocus Sequence Typing; Genes, Bacterial; Computer Simulation; Disease Outbreaks; zastoupení bazí; jednonukleotidový polymorfismus; Genotyping Techniques; Whole Genome Sequencing; Escherichia coli; genotypizační techniky; Base Composition; sekvenování celého genomu; DNA, Bacterial; Repetitive Sequences, Nucleic Acid; počítačová simulace; Nucleic Acid Denaturation; multilokusová sekvenční typizace; bakteriální geny; polymerázová řetězová reakce; Czech Republic; DNA Primers; Polymerase Chain Reaction; Bacterial Typing Techniques; Population Surveillance; Genome, Bacterial; Česká republika; epidemický výskyt choroby; techniky typizace bakterií